Importance of teaching and research from the academic perspective in Mexican public institution: The case of the University of Sonora - Estévez Nenninger, Etty Haydee; Martínez García, Joel Manuel (Education Policy Analysis Archives, 2011)
This paper contains an analysis of the importance of teaching and research activities at the University of Sonora (UNISON), from the academic perspective. During 2007 the survey "Reconfiguration of Academic Profession in Mexico" (RPAM) was applied on a representative sample of full-time teachers of UNISON, public higher institution which happens to be one of the most important universities of northwestern México. The academic features of both teaching and research were considered separately, and then sought for some relations between these two activities, to finally make a comparative analysis with the national survey results. The UNISON faculty is mainly composed by adulthood (51.8 years average), labor experienced (23 years in working place) and a high rate in educational levels: 20.2 % bachelor degree, 53.2% master, 26.5% doctorate). The presence of academic women throws a 33% of faculty, lower than the average shown by the national survey (37%). Given the classification scheme proposed in this paper, it was possible to clearly identify four types of scholars which set a pattern that might be present in other public state institutions of the country, this according to the differential importance assigned to the various activities, roles and responsibilities that make up academic work.